Enhanced Versus Conventional Sludge Anaerobic Processes: Performances and Techno‐Economic Assessment. (1st May 2016) - Gianico, Andrea; Bertanza, Giorgio; Braguglia, Camilla M.; Canato, Matteo; Gallipoli, Agata; Laera, Giuseppe; Levantesi, Caterina; Mininni, Giuseppe
ABSTRACT: : Sewage sludge processing is a key issue in water resource recovery facilities due to the inefficacy of conventional treatments to produce high quality biosolids to be safely used in agriculture. Under this framework, the performances of several enhanced stabilization processes, namely ultrasound‐pretreated Mesophilic Anaerobic Digestion (US+MAD), thermophilic anaerobic digestion (TAD), thermal‐pretreated TAD (TH+TAD) and ultrasound‐pretreated inverse Temperature Phased Anaerobic Digestion (US+iTPAD) have been investigated. Such enhanced processes resulted in higher biogas yields and higher destruction of pathogens with respect to conventional MAD process, thus suggesting their feasibility in full‐scale implementation perspectives. A procedure for technical‐economic comparison of new sludge processing lines against conventional ones (benchmarking) was developed, based on the definition of technical issues (e.g. reliability, complexity, etc.) which are rated for each situation. Moreover, capital and operating costs were estimated. The enhanced processes analyzed in this work showed some potentially critical items, mainly related to energy balance and reagent consumption.